Pediatric Surgical Care During the COVID-19 Lockdown: What Has Changed and Future Perspectives for Restarting in Italy. The Point of View of the Italian Society of Pediatric Surgery - Morini, Francesco; Romeo, Carmelo; Chiarenza, Fabio; Esposito, Ciro; Gamba, Piergiorgio; Gennari, Fabrizio; Inserra, Alessandro; Cobellis, Giovanni; Leva, Ernesto; Angotti, Rossella; Raffaele, Alessandro; Cacciaguerra, Sebastiano; et al. (Frontiers in Pediatrics, 2022)
Background: The coronavirus disease 2019 (COVID-19) time exacerbated some of the conditions already considered critical in pediatric health assistance before the pandemic. A new form of pediatric social abandonment has arisen leading to diagnostic delays in surgical disorders and a lack of support for the chronic ones. Health services were interrupted and ministerial appointments for pediatric surgical healthcare reprogramming were postponed. As a result, any determination to regulate the term “pediatric” specificity was lost. The aim is, while facing the critical issues exacerbated by the COVID-19 pandemic, to rebuild future perspectives of pediatric surgical care in Italy. Methods Each Pediatric Society, including the Italian Society of Pediatric Surgery (SICP), was asked by the Italian Federation of Pediatric Associations and Scientific Societies to fill a questionnaire, including the following the main issues: evaluation of pre-pandemic criticalities, pediatric care during the pandemic and recovery, and current criticalities. The future care model of our specialty was analyzed in the second part of the questionnaire. Results Children are seriously penalized both for surgical treatment as well as for the diagnostic component. In most centers, the pediatric surgical teams have been integrated with the adult ones and the specificity of training the pediatric operating nursing is in danger of survival. “Emotional” management of the child is not considered by the general management and the child has become again an adults patient of reduced size. Conclusion A new functional pediatric surgical model needs to be established in general hospitals, including activities for day surgery and outpatient surgery. To support the care of the fragile child, a national health plan for the pediatric surgery is required.